Análise da estabilidade estatíca e dinâmica de vigas pelo método dos elementos de contorno - Passos, José Jarbson Salustiano dos (2014)
In this work new solutions based on the direct Boundary Element Method (BEM) for static and dynamic stability beam problems are presented. Both Euler-Bernoulli and Timoshenko models are used to represent the beam responses. All discussions on mathematical steps to write down the BEM representation are presented. Alternative fundamental solutions for static and dynamic Euler-Bernoulli beam stability problems are proposed, resulting in the simpler forms than conventional fundamental solutions commonly used for the problems. In addition, the effects of Pasternak elastic foundations are incorporated into the expressions of proposed fundamental solutions. For the case of the Timoshenko static and dinamic stability, all the direct BEM representation (integral equations, fundamental solutions and algebraic equations) here proposed are inovative. Their fundamental solutions incorporate Pasternak foundation effects as well. A convenient strategy is also presented in order to deal with elastic end supports and discontinuities at beam domain such as abrupt change of cross section geometry (stepped beams), internetiated axial load, rigid or elastic supports at beam domain. Numerical examples incorporating various types of boundary conditions and domain discontinuities in order to validate the proposed BEM solution are presented.